4-H Energy Encounters Leader's Guide - Linda Barber; Marilyn Simmons; Craig R. Miller (EDIS)
4-H ENERGY ENCOUNTERS was developed through a team effort of the Department of 4-H and Other Youth Programs, Institute of Food and Agricultural Sciences, University of Florida. Printed on April, 1993 and May, 1996; reviewed in 2002.